Model Matematika Free Throw pada Permainan Bola Basket - Saputra, Yogi Trio; Rosha, Media (Journal of Mathematics UNP, 2023)
In basketball, basic skills such as Passing, Dribbling, Rebound, and Shooting are crucial. Shooting includes various techniques like one hand set shoot, jump shot, lay up, hook shot, runner, three-point shot, and free throw. A free throw is an unguarded shot that awards one point if successful. One of the factors that affects the success of executing a free throw is understanding the physics principles involved, such as parabolic motion, Magnus effect, gravitational force, and friction when the ball is in the air. During a free throw, the ball moves in three dimensions (3D). This applied research utilized secondary data and the numerical method of Runge-Kutta to determine the optimal trajectory of the ball during a free throw. The results indicate that an initial velocity of 10 m/s with a spin frequency of 3 rot/s and a shooting angle of 30°, as well as a shooting angle of 48° with a spin frequency of 3 rot/s and an initial velocity of 8 m/s, provide the best trajectory for scoring points.